PAPR Reduction Using Eight Factors Rotating Phase Shift Technique Based on Local Search Algorithm in OFDM - Nahar, Ali Kareem; Abdalla, Ahmed N; Jaber, Ali Y; Ezzaldean, Mohammed Moanes (Review of Computer Engineering Research, 2017)
Orthogonal frequency division multiplexing (OFDM), Multi-Carrier (MC) system, is a popular standard in wireless communication for its enabling high throughput data transfer. However, the MC signal usually has a high peak-to-average power ratio (PAPR), which involves a wide-dynamic-range, power consuming amplifier. Whenever the signal height is greater than the amplified linear region, the signal is distorted. In this paper, propose a novel scheme that rotating phase shift (RPS) technique based signal scrambling is proposed to reduce PAPR in OFDM systems. In addition, the pilot phase signal is picked out by RPS technique applied new algorithm the local research to alleviate scrambling information corruption and show discernible advancements. So, our technique improves over the existing ones in the same category. The transmitted signal of OFDM is tested with Mobile WiMAX IEEE 802.16e standard, that compared the various phase shift with a slight computational complexity is studied. The simulation result shows that original signal at pilot-assisted QAM is capable of bringing down the electrical PAPR by about 3.5 times as a modest complementary cumulative distribution function (CCDF) point of 10-3 for M=8 low complexity. In addition, the best phase-shift factor was selected to reduce the monetary value of computational complexity.